Deaf and technology: A bibliometric analysis of scientific literature - Bojana Vuković; Sladjana Ćalasan; Andrea Vegar; Sanja Živanović (Биомедицинска истраживања, 2022)
Introduction: Technology has the potential to reduce isolation, increase independence, provide educational, financial and social opportunities for users, but there may still be barriers, especially for people with disabilities or sensory deficits. Therefore, it is very important to determine what science has been dealing with in this area, more precisely in the area of the deaf. The main aim of this paper was to map the progress and trends of scientific literature in the field of technology for the deaf (children and adults). Methods: A bibliometric analysis in VosViewer was performed to determine the set goals. The Dimensions database was chosen for literature analysis. The unit of analysis consisted of 1242 publications and VosViewer was applied. Results: The results show that this topic in science has experienced exponential growth in the last decade. Also, the most productive authors, journals, institutions and countries, as well as their collaboration network, were identified through a visual analysis of co-citations. Based on the analysis of co-words, we can draw a conclusion that the words: student, sign language, cochlear implant, classroom, parent, outcome are the most frequently repeated words, which would mean that the topics covered in this domain are mainly focused on children and their functioning in the environment and school system. Conclusion: Providing the main lines of research generated in this field allows scientists to follow the trends themselves. Also, therapists can use our analysis to identify sources that can indicate how and in what context deaf children can use technology.
Keywords: deaf; technology; VosViewer